Extracurricular Educational Programs and School Readiness: Evidence from a Quasi-Experiment with Preschool Children - Anna Makles; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper adds to the literature on extracurricular early childhood education and child development by exploiting unique data on an educational project in Germany, the Junior University (JU). Utilizing a quasi-experimental study design, we estimate the causal short-run effect of JU enrollment on ability measures and show that attending extra science courses with preschool classes leads to significantly higher school readiness. Attending classes at JU increases school readiness by approximately 2.18% which corresponds to 1/5 of a standard deviation of the ability score. The result is plausible and passes various robustness checks.
Keywords: I20; I21; I28; J13; 330; early childhood education; extracurricular activities; early interventions; school readiness